Fibre optic Bragg grating sensors: a new technology for smart structure monitoring in Malaysia - Abdul Rahman, Rosly; Ikhsan, Sabirin; Muhamad Supian, Hairurizal (2000)
Optical fibres are well known for their importance as transporter of information. However, much has been said and proved that optical fibres are essential and play their role as producers of information, that is as sensors. Recent research has proved that fibre optic sensors can be integrated in structure such as multistorey buildings, dams and bridges with the capability to monitor their strength and integrity. One component that is increasingly being used in communication and sensing is Bragg grating. A study in the implementation of a fibre optics Bragg grating (FOBG) sensors system is discussed in this paper. This study concentrates on the issues related to the utilization of FOBG sensors in smart structures